2021
DOI: 10.1093/nar/gkab1246
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation of the impact of core sequence on immobile DNA four-way junction structure and dynamics

Abstract: Immobile four-way junctions (4WJs) are core structural motifs employed in the design of programmed DNA assemblies. Understanding the impact of sequence on their equilibrium structure and flexibility is important to informing the design of complex DNA architectures. While core junction sequence is known to impact the preferences for the two possible isomeric states that junctions reside in, previous investigations have not quantified these preferences based on molecular-level interactions. Here, we use all-atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…Furthermore, MD simulations of Holliday junctions have also been performed. 44,[57][58][59] Mathur et al has showed that MD simulations of dyes attached to the Holliday junctions of large DNA bundles can yield dye orientations in agreement with experimental uorescence data. 44 Wheatley et al found that isolated, four-arm Holliday junctions initialized in an open conformation stabilize in a stacked conguration at both high and low salt concentrations, indicating that MD is able to capture the conformational transitions of the Holliday junction.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Furthermore, MD simulations of Holliday junctions have also been performed. 44,[57][58][59] Mathur et al has showed that MD simulations of dyes attached to the Holliday junctions of large DNA bundles can yield dye orientations in agreement with experimental uorescence data. 44 Wheatley et al found that isolated, four-arm Holliday junctions initialized in an open conformation stabilize in a stacked conguration at both high and low salt concentrations, indicating that MD is able to capture the conformational transitions of the Holliday junction.…”
Section: Introductionmentioning
confidence: 63%
“…Typical Holliday junction IDAs and twist angles fall in the range of ∼60° and ∼40–60°, respectively. 57–59,82 It should be noted that these values are for Holliday junctions without dyes attached to the DNA backbone – the dyes in our study act as an additional base or spacer in the DNA sequence, which may affect the DNA dynamics and conformations. This could lead to discrepancies observed between pure DNA Holliday junctions and Holliday junctions with dyes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Theoretical computational guides highlight an important role in investigating the molecular structure and electronic properties of a wide range of highly functionalized systems [1][2][3][4]. The detailed computational experience was taken from using the most advanced wave function methods such as the most popular one, density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…The detailed computational experience was taken from using the most advanced wave function methods such as the most popular one, density functional theory (DFT). For highly functionalized systems such as pyridopyrimidines [1,2,[4][5][6] triazole, and [1][2][3][4] tetrazole derivatives, these types of compounds are interesting for different biological applications such as anti-microbial and cytotoxic activities [7]. Several studies are concerned with the causes and solving different types of cancer problems and how to limit their occurrence.…”
Section: Introductionmentioning
confidence: 99%